The influence of cultural identity on achieving sustainable urban development in developing countries - Cobbina, Edward John; Ametepey, Simon Ofori; Aigbavboa, Clinton; Frempong-Jnr, Emmanuel Yaw; Thwala, Wellington Didibhuku; Ebekozien, Andrew; Addy, Hutton (Frontiers in Built Environment, 2025)
PurposeAn urban center’s cultural identity (CI) is the tangible and intangible elements instituted and incorporated in the urban placemaking process to provide individuals or groups with their identity, sense of belonging, and ownership. With recent trends in urban growth, especially in developing countries, an in-depth understanding of the elements or determinants of urban development that will ensure a sustainable urban environment has become critical in the global development discussion. This study investigates the influence of CI and its essential elements of sustainable urban development (SUD).Design/methodology/approachA quantitative research method using closed-ended questions from a questionnaire survey was utilized to solicit responses from sampled professionals within the urban planning and development space in four urban centers in Ghana. The data obtained were analyzed by employing exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modeling (SEM) to establish the influence of CI and its elements in achieving SUD and to explain the common underlying dimensions of the elements.FindingsThe findings highlight that elements associated with government initiative and support systems and effective institutional structure for cultural development under cultural identity were identified as the most critical elements that influence the achievement of SUD. Furthermore, the hypothesis tested revealed a strong influence of CI in achieving SUD in developing countries.Research limitations/implicationsThis study is confined to the influence of CI and its essential elements of SUD.Practical implicationsAs part of the practical implications, the study suggests the strong need to consider CI and its elements in the urban placemaking process to attain SUD.Originality/valueIn addition to findings influencing CI and its essential elements of SUD in developing countries, using Ghana as a case study, the study indicates that government initiatives and support systems and institutional structures for promoting and protecting culture are relevant and influential in achieving SUD in developing countries.